PELATIHAN INSTALASI LISTRIK DAN SOSIALISASI PERSYARATAN UMUM INSTALASI LISTRIK (PUIL) 2011 DI DESA WANINGGAP NANGGO DISTRIK SEMANGGA KABUPATEN MERAUKE PROVINSI PAPUA - Rusli Rusli; Andi Azizah (Musamus Devotion Journal, 2019)
The problem that occurs in the village of Waninggap Nanggo is the absence of electricians in the area so that if there is an electrical disturbance in their homes they should contact the Perusahaan listrik Negara (PLN) to deal with electrical disturbances. The distance from the PLN office (around 30 KM) to the village of Waninggap Nanggo has resulted in the community having to wait longer to repair the electrical installation. The lack of means of transportation to the village is also an obstacle for the community in obtaining service facilities from PLN. The aim of the Program Kemitraan Masyarakat (PKM) is to provide knowledge and skills for youth groups in the Waninggap Nanggo Village so that they can have skills regarding electrical installations. In addition, we will also provide Socialization on 2011 Electrical Installation General Requirements (PUIL 2011). With the hope of this activity the youth in the Village can master the Standard Installation of Electrical Installation so that they are expected to be able to apply knowledge and skills to be applied to other youth groups. This activity is carried out in stages starting from the field observations that we have done, the training plan will be carried out at the Village Hall and directly practice the improvement of electrical installations in the homes of people whose electrical installations are not in accordance with the Standards